2020
DOI: 10.1371/journal.pone.0229998
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating adiponectin is an independent disease activity marker in patients with rheumatoid arthritis: A cross-sectional study using the KURAMA database

Abstract: Objective To clarify the relationship among serum adiponectin, body composition, current disease activity and therapeutics of rheumatoid arthritis (RA). Methods We conducted a cross-sectional study in RA patients under treatment with agents including biological disease-modifying antirheumatic drugs (bDMARDs) and Janus kinase (JAK) inhibitors. A total of 351 subjects from the Kyoto University RA Management Alliance cohort (KURAMA) were enrolled in the analysis. We classified the participants into five body comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…However, most studies have shown a correlation of adiponectin with inflammation markers such as C-reactive protein (CRP), including a recent study showing that total and HMW adiponectin are positively correlated with CRP levels [ 47 ]. A positive correlation between serum adiponectin and the disease activity score disease activity score (DAS)28 - ESR in RA patients was shown in another cross-sectional study [ 48 ]. Interestingly, subcutaneous adipose tissue from RA patients produced more adiponectin compared to OA patients and correlated with disease activity and disease duration in these patients [ 49 ].…”
Section: Adipokines In Autoimmune Rheumatoid Arthritismentioning
confidence: 99%
“…However, most studies have shown a correlation of adiponectin with inflammation markers such as C-reactive protein (CRP), including a recent study showing that total and HMW adiponectin are positively correlated with CRP levels [ 47 ]. A positive correlation between serum adiponectin and the disease activity score disease activity score (DAS)28 - ESR in RA patients was shown in another cross-sectional study [ 48 ]. Interestingly, subcutaneous adipose tissue from RA patients produced more adiponectin compared to OA patients and correlated with disease activity and disease duration in these patients [ 49 ].…”
Section: Adipokines In Autoimmune Rheumatoid Arthritismentioning
confidence: 99%
“…Rheumatoid arthritis (RA), the most common form of inflammatory arthritis, is a chronic systemic autoimmune disease characterized by aggressive symmetrical inflammation of multiple joints ( Kobayashi et al, 2010 ; Miossec, 2013 ; Minamino et al, 2020 ). Epidemiological studies have shown that about 90% of RA patients develop bone erosion within 2 years of onset, resulting in joint deformity or even disability.…”
Section: Obesity and Bone-related Diseasesmentioning
confidence: 99%
“…Therefore is the observation that autologous serum eye drops can, at least temporarily, successfully be replaced by HMW HA eye drops [126] clinically important and very promising. Serum, on the other hand, is used as a diagnostic medium as it may reflect general disease [127]. Hence, pathological conditions of the patient could also alter the blood composition and possibly result in a pathological composition of the serum.…”
Section: Epithelial Lesions-the Effect Of Attritionmentioning
confidence: 99%